The Effect of Transformational Leadership Style and Compensation Through Organizational Citizenship Behavior (OCB) on Employee Performance BPJS Employment Banyuwangi Branch - Citra Ayu Pratiwi; Hary Sulaksono; Tamriatin Hidayah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine and analyze the influence of transformational leadership style and compensation on employee performance through organizational citizenship behavior (OCB) at the BPJS Ketenagakerjaan Banyuwangi Branch Office. The research employs a quantitative approach using questionnaires for data collection and is tested using the Structural Equation Modeling (SEM) method with the WarpPLS 7.0 application. The results of the study indicate that: 1. Transformational leadership style has a positive effect on OCB at BPJS Ketenagakerjaan KC Banyuwangi. 2. Compensation has a positive effect on OCB. 3. Transformational leadership style has a positive effect on employee performance. 4. Compensation has a positive effect on employee performance. 5. OCB has a positive effect on employee performance. 6. OCB mediates the influence of transformational leadership style on employee performance. 7. OCB mediates the influence of compensation on employee performance. These findings provide guidance for organizations in managing leadership, compensation, and work culture to improve employee performance. From an academic perspective, this study enriches theories on leadership, compensation, OCB, and employee performance by providing empirical evidence that OCB plays a mediating role in these relationships.